PENGARUH MODEL PEMBELAJARAN TERPADU DAN GAYA KOGNITIF TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SDN CAWANG 03 PAGI - Ritonga, Rudi (Jurnal Pendidikan Guru, 2017)
This study aims to determine the effect of integrated learning and cognitive style on learning outcomes of IPS students, integrated learning is a model of spider webs (webbed) and a model connected (connected) while the cognitive style consists of field dependent and field independent. This research was conducted in class IVa, IVb Elementary School 03 am Jakata Cawang East semester academic year 2013/2014. The study involved 68 students in the sample were selected grouping rough. Data collected using the instrument in the form of multiple-choice tests .The data obtained was analyzed using Two Way ANAVA method. The study revealed the following conclusions: (1) The results of social studies taught a group of students learning model cobwebs (webbed) students are taught higher connectednes s model (connected), (2) learning outcomes IPS group of students who have cognitive style field dependent higher than the group of students who choose a field independent cognitive styles. (3)There is an interaction effect between the use of an integrated model of learning and cognitive style on learning outcomes IPS. (4)For groups of students are given learning model cobwebs (webbed), learning outcomes between students who have a field-dependent cognitive style higher than in the group of students who have a field-independent cognitive styles. (5) For a given group of students learning model model of connectedness (connected), IPS learning outcomes between students who have a field-dependent cognitive style higher than the students who have the cognitive style field-independet. (6) For students who have cognitive style dependet, social studies outcomes between groups of students are given learning model cobwebs (webbed) is higher than that given to the student learning model of connectedness (connected). (7) For a group of students who have a field-dependent cognitive style, learning outcomes between students who are awarded IPS learning model cobwebs (webbed) is higher than that given to the student learning model of connectedness (connected)